Recent advances in sustainable process design and optimization : with CD-ROM - Foo, Dominic C. Y.; El-Halwagi, Mahmoud M., 1962-; Tan, Raymond R. (Advances in process systems engineering, 2012)
This book is a compilation of the various recently developed techniques emphasizing better chemical processes and products, with state-of-the-art contributions by world-renowned leaders in process design and optimization. It covers various areas such as grass-roots design, retrofitting, continuous and batch processing, energy efficiency, separations, and pollution prevention, striking a balance between fundamental techniques and applications. The book also contains industrial applications and will serve as a good compilation of recent industrial experience for which the process design and optimization techniques were applied to enhance sustainability. Academic researchers and industrial practitioners will find this book useful as a review of systematic approaches and best practices in sustainable design and optimization of industrial processes. The book is accompanied by some electronic supplements (i.e., models and programs) for selected chapters.